La sustancia: capitalismo, salud, corporalidad y régimen neoliberal - Araya-Vargas, Sebastián Alberto (Pontificia Universidad Católica del Perú, 2025)
In this review of the film La sustancia (2024), I analyze several key moments in the film based on contributions from the anthropology of the body and health. First, I examine the relationship between the protagonist and her boss as a dynamic inherited from the early days of capitalism. Next, I explore how the film shows that the demands of capital affect the definition of a healthy body, which is determined by factors such as youth, beauty, and productivity. Finally, I offer an interpretation of the meaning of “the substance” within the context of the contemporary neoliberal regime.

En esta reseña de la película La sustancia (2024), analizo diversos momentos clave de la cinta a partir de los aportes de la antropología del cuerpo y la salud. En primer lugar, examino la relación entre la protagonista y su jefe como una dinámica heredada de los inicios del capitalismo. En segundo lugar, explico cómo el filme evidencia que las demandas del capital influyen en la definición de un cuerpo saludable, el cual es determinado por elementos como la juventud, la belleza y la productividad. Por último, presento una interpretación del significado de “la sustancia” enmarcado en el régimen neoliberal contemporáneo.
The substance: capitalism, health, corporeality, and the neoliberal regime
Keywords: Anthropology of the body; Anthropology of health; Capitalism; Neoliberalism; Power; Antropología del cuerpo; Antropología de la salud; Capitalismo; Neoliberalismo; Poder; https://purl.org/pe-repo/ocde/ford#5.04.03